2022
DOI: 10.3390/app12031351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonic Pulses on the Functional Properties of Stickwater

Abstract: Large volumes of waste are generated in the processing operations of the fishing industry. These effluents contain potentially useful proteins. However, it is necessary to concentrate them for utilization. The stickwater (SW) resulting from this operation was subjected to a protein-fractionation step, pH adjustment (acid + alkaline) and ultrasonic pulsing in order to aid in hydrolysis and evaluate its functional and nutritional properties. The protein fractions, as well as the protein hydrolysates present in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…Finally, the UAE treatment decreased the FRAP activity in a significant way either in almond samples (from 2446 ± 23.08% in CtrlA to 1362 ± 23.08% in UltraSA at 0.075 mg/mL) or in coconut samples (from 2400 ± 23.08% in CtrlC to 1823 ± 18.31% in UltraSC at 0.03 mg/mL) ( Figure 6 C). The reduction is probably related to the presence of chelating amino acids in the protein sequence (Cis, His, Glu) [ 46 ]. Previously ( Figure 3 B), we showed that the UAE reduced the content of free SH groups positioned on the surface of coconut and almond proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the UAE treatment decreased the FRAP activity in a significant way either in almond samples (from 2446 ± 23.08% in CtrlA to 1362 ± 23.08% in UltraSA at 0.075 mg/mL) or in coconut samples (from 2400 ± 23.08% in CtrlC to 1823 ± 18.31% in UltraSC at 0.03 mg/mL) ( Figure 6 C). The reduction is probably related to the presence of chelating amino acids in the protein sequence (Cis, His, Glu) [ 46 ]. Previously ( Figure 3 B), we showed that the UAE reduced the content of free SH groups positioned on the surface of coconut and almond proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Habitualmente está conformada del 8-10% de sólidos totales, 5.6% de proteína, 0.6% de grasa, 1.8% de cenizas y 92% de humedad (Goycoolea et al, 1997) respectivamente (Bechtel, 2005). Estos resultados son más altos que los reportados para las aguas de cocción del camarón (53%) (Pérez-Santín, Calvo, López-Caballero, Montero & Gómez-Guillén, 2013), para los del AC del atún, la anchoveta y el pescado silvestre (65%) (Cadena-Cadena et al, 2022;Wu et al, 2018) y que para los del AC de la sardina y el jugo de cocción del atún (56%) (Martínez-Montaño et al, 2021), así como para los de Kilka clupeonella (70%). Esta variación puede ser atribuida a diversos factores como la formación de los complejos de proteína-quitina, proteína-lípidos o proteínapigmentos, a la especie de pescado, a la época de captura, a las condiciones fisiológicas del organismo (el estado sexual de la población), a las condiciones de almacenamiento y de operación durante la elaboración del producto final, lo que resulta en un incremento de la concentración proteica (Bechtel, 2005;Mahdabi & Hosseini Shekarabi, 2018;Martínez-Montaño et al, 2021).…”
Section: Tratamientos Para Las Aguas Residualesunclassified